The ugly face of tourism: Marine debris pollution linked to visitation in the southern Great Barrier Reef, Australia. Issue 1 (15th April 2017) - Wilson, Scott P.; Verlis, Krista M.
Abstract: Marine debris is one of the most significant issues facing oceans worldwide. The sources of this debris vary depending on proximity to urban centres and the nature of activities within an area. This paper examines the influence of tourism in the southern Great Barrier Reef (GBR), and its contribution to litter levels in the region. By conducting beach debris surveys on occupied and unoccupied islands, this study found that debris was prevalent throughout the region with significant differences in material types between locations. The greatest source of debris from publically accessible islands was tourist-related, with this source also influencing debris loads on nearby uninhabited islands. A focus on debris at Heron Island, showed that sites close to amenities had greater levels of tourist-sourced items like cigarette butts. These findings indicate the contribution of tourists to this problem and that working with operators and managers is needed to minimise visitor impacts. Graphical abstract: Highlights: Tourists were the source of most debris at publically accessible GBR islands. Zones closest to tourist infrastructure had more tourist-sourced items. Tourists in an area influenced the type of debris on restricted access islands. Education and awareness programmes targeting tourists in the region are needed.